1985
DOI: 10.1111/j.1365-246x.1985.tb05117.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric soundings over a Precambrian contact in Australia

Abstract: The Willyama Complex near Broken Hill represents a major exposure of the Precambrian terrain in Australia. However, the eastern limits are obscured by recent cover in the Murray/Darling basin. The nature and extent of the contact with the younger basement to the east is unknown.Magnetotelluric data have now been obtained as an aid to regional mapping. Profiles are based on observations at 14 sites in a traverse east of Broken Hill. Apparent resistivities presented as pseudosections reflect the major structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
(19 reference statements)
0
21
0
1
Order By: Relevance
“…Probably, this is one of the main reasons that relatively fewer field surveys for electrical anisotropy than for electrical depth structure have been carried out. It is not known whether electrical anisotropy in the lower continental crust appears on a global scale; however, the few reports available do show horizontal electrical anisotropy beneath several places in conjunction with high electrical conductivity up to 0.01-0.1 S/m along certain directions, e.g., at Australia shield, Fennoscandian (Baltic) shield, Saxothuringia in central Germany, and Rhenish shield in western Germany (Cull 1985;Rasmussen 1988;Kellett et al 1992;Bahr et al 2000;Leibecker et al 2002).…”
Section: Electrical Anisotropy Of the Lower Continental Crustmentioning
confidence: 96%
See 3 more Smart Citations
“…Probably, this is one of the main reasons that relatively fewer field surveys for electrical anisotropy than for electrical depth structure have been carried out. It is not known whether electrical anisotropy in the lower continental crust appears on a global scale; however, the few reports available do show horizontal electrical anisotropy beneath several places in conjunction with high electrical conductivity up to 0.01-0.1 S/m along certain directions, e.g., at Australia shield, Fennoscandian (Baltic) shield, Saxothuringia in central Germany, and Rhenish shield in western Germany (Cull 1985;Rasmussen 1988;Kellett et al 1992;Bahr et al 2000;Leibecker et al 2002).…”
Section: Electrical Anisotropy Of the Lower Continental Crustmentioning
confidence: 96%
“…This is basically consistent with the reported values of *3 to [20 in the lower continental crust, especially in recent years (Rasmussen 1988;Kellett et al 1992;Bahr et al 2000;Leibecker et al 2002), considering the uncertainty in MT and GDS field surveys and the technical problems in resolving electrical conductivity and layer thickness of conductive zones as pointed out above. In one of the earliest studies by Cull (1985), an anisotropy factor of 400 was reported for the lower crust (at depths of 15-35 km) beneath the Australia shield, which was probably caused by serious technical problems in both the measurement and inversion modeling involved in this very early work. So far, no systematic studies have been conducted on the preferred orientations of plagioclase in the lower continental crust, e.g., on representative mafic xenolith granulites, and thus the possible contribution of hydrous plagioclase to geophysically resolved deep crustal electrical anisotropy requires further investigations.…”
Section: Electrical Anisotropy Of the Lower Continental Crustmentioning
confidence: 96%
See 2 more Smart Citations
“…The source used for information on ocean depth is the GEBCO (1982) 1:10000000 chart of the oceans in the Australian region. (Cull & Spence 1983) and, on other con- Figure 1 which shows a simple configuration of 60 m of weathered zone (o= 10"' S.m' 1 ) overlying a crystalline craton (a = 2X 10~4 S.m" 1 ) adjacent to a sediment-filled graben 5000 m thick (a = 10"' S.m" 1 ); the graben is underlain by a resistive basement (a = 10~3 S.m" 1 )-The base of the sheet is at depth 10 km.…”
Section: Australia In Its Surrounding Seasmentioning
confidence: 97%